2015
DOI: 10.2337/db15-0060
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Disruption of Protein Kinase STK25 Ameliorates Metabolic Defects in a Diet-Induced Type 2 Diabetes Model

Abstract: Understanding the molecular networks controlling ectopic lipid deposition, glucose tolerance, and insulin sensitivity is essential to identifying new pharmacological approaches to treat type 2 diabetes. We recently identified serine/threonine protein kinase 25 (STK25) as a negative regulator of glucose and insulin homeostasis based on observations in myoblasts with acute depletion of STK25 and in STK25-overexpressing transgenic mice. Here, we challenged Stk25 knockout mice and wild-type littermates with a high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
88
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 52 publications
(108 citation statements)
references
References 52 publications
19
88
1
Order By: Relevance
“…Conversely, we found that siRNA knockdown of STK25 in IHHs and HepG2 cells attenuated lipid accumulation by stimulating β-oxidation and TAG secretion and inhibiting TAG synthesis. Consistent with these results, we observed augmented hepatic β-oxidation and VLDL-TAG export in Stk25-knockout mice fed a high-fat diet, extending the results from our earlier studies showing that Stk25 −/− mice are protected against dietinduced liver steatosis [7]. Moreover, we found a statistically significant positive association between STK25 mRNA expression and fat content in human liver.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Conversely, we found that siRNA knockdown of STK25 in IHHs and HepG2 cells attenuated lipid accumulation by stimulating β-oxidation and TAG secretion and inhibiting TAG synthesis. Consistent with these results, we observed augmented hepatic β-oxidation and VLDL-TAG export in Stk25-knockout mice fed a high-fat diet, extending the results from our earlier studies showing that Stk25 −/− mice are protected against dietinduced liver steatosis [7]. Moreover, we found a statistically significant positive association between STK25 mRNA expression and fat content in human liver.…”
Section: Discussionsupporting
confidence: 81%
“…Knockdown of STK25 reduces lipid deposition in IHHs and HepG2 cells via increased β-oxidation and TAG secretion combined with repressed lipid synthesis Our recent studies demonstrate that mice with genetic disruption of STK25 are protected from diet-induced liver steatosis [7]. To investigate the impact of STK25 knockdown on lipid metabolism in human hepatocytes, we transfected IHHs and HepG2 cells with STK25-specific siRNA or with a non-targeting control (NTC) siRNA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations